2017
DOI: 10.1134/s1063773717080059
|View full text |Cite
|
Sign up to set email alerts
|

Pulsations of intermediate–mass stars on the asymptotic giant branch

Abstract: Evolutionary tracks from the zero age main sequence to the asymptotic giant branch were computed for stars with initial masses 2M ⊙ ≤ M ZAMS ≤ 5M ⊙ and metallicity Z = 0.02. Some models of evolutionary sequences were used as initial conditions for equations of radiation hydrodynamics and turbulent convection describing radial stellar pulsations. The early asymptotic giant branch stars are shown to pulsate in the fundamental mode with periods 30 day Π 400 day. The rate of period change gradually increases as th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…As in our earlier studies devoted to nonlinear pulsations of AGB stars (Fadeyev, 2017;2018) the pulsation period Π was determined using the discrete Fourier transform of the kinetic energy of the pulsating stellar envelope. Thus, the period estimate of each hydrodynamic model was obtained by averaging over the time interval of the solution of the equations of hydrodynamics.…”
Section: Hydrodynamic Models Of Post-agb Starsmentioning
confidence: 99%
“…As in our earlier studies devoted to nonlinear pulsations of AGB stars (Fadeyev, 2017;2018) the pulsation period Π was determined using the discrete Fourier transform of the kinetic energy of the pulsating stellar envelope. Thus, the period estimate of each hydrodynamic model was obtained by averaging over the time interval of the solution of the equations of hydrodynamics.…”
Section: Hydrodynamic Models Of Post-agb Starsmentioning
confidence: 99%
“…In our previous work (Fadeyev 2017), we investigated hydrodynamic models of stars with initial masses 2M ⊙ ≤ M ZAMS ≤ 5M ⊙ on the stage of thermal instability of the helium burning shell (TP-AGB). In particular, it was shown that reduction of the pulsation period in T UMi 2 cannot be explained by models with initial mass M ZAMS > 2M ⊙ .…”
Section: Introductionmentioning
confidence: 99%
“…The mean time interval between helium flashes depends on the stellar mass and ranges from 10 4 to 10 5 yr (Herwig 2000;Weiss, Ferguson 2009), whereas the time scale of the changes in the helium burning shell luminosity is ≤ 10 3 yr (Wood, Zarro, 1981; Boothroyd, Sackmann 1988). One of the consequences of thermal instability is secular period change observed in some Miras because during the short-term variation of the helium burning shell luminosity the stellar radius varies by as much as a factor of three (Wood, Zarro, 1981;Fadeyev 2016Fadeyev , 2017.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations